Doctor's follow-up after stroke in the south of Sweden: An observational study from the Swedish stroke register (Riksstroke). (June 2016) - Ullberg, Teresa; Zia, Elisabet; Petersson, Jesper; Norrving, Bo
Introduction: Information on follow-up practices after stroke in clinical routine are sparse. We studied the probability of doctor's follow-up within 90, 120, 180, and 365 days after hospital discharge, and how patient characteristics were associated with the probability of follow-up, in a large unselected stroke cohort. Patients and methods: Data on patients living in southern Sweden, hospitalized with acute ischemic stroke or intracerebral hemorrhage 1 January 2008 to 31 December 2010, were obtained from the Swedish stroke register (Riksstroke) and merged with administrative data on doctor's visits during the year following stroke. Results: Complete data were registered in 8164 patients. The cumulative probability of a doctor's follow-up was 76.3% within 90 days, 83.6% within 120 days, 88.7% within 180 days, and 93.1% within 365 days. Using Cox regression calculating hazard ratios (HR), factors associated with 90-day follow-up were: female sex HR = 1.066 (95%CI: 1.014–1.121), age: ages 65–74 HR = 0.928 (95%CI: 0.863–0.999), ages 75–84 HR = 0.943 (95%CI: 0.880–1.011), ages 85 + HR = 0.836 (95%CI: 0.774–0.904), pre-stroke dependency in activities of daily living (ADL): HR = 0.902 (95%CI = 0.819–0.994), prior stroke HR = 0.902 (95%CI: 0.764–0.872), and severe stroke HR = 0.506 (95%CI: 0.407–0.629). In patients discharged to assisted living, the following factors were associated with lower follow-up probability: living alone pre-stroke HR = 0.836 (95%CI: 0.736–0.949), and pre-stroke dependency HR = 0.887 (95%CI: 0.775–0.991). Discussion: This study was based on hospital administrative data of post-stroke doctor's visits, but may be confounded by attendance for other conditions than stroke. Conclusions: One in four stroke patients was not followed up within three months after hospital discharge. Vulnerable patients with high age, pre-stroke ADL dependency, and prior stroke were less likely to receive doctor's follow-up.